The balance between effectiveness and proportionality in responding to online disinformation at crossroads: An analysis of the response of the European Union through security governance, 2015-2022 - Geraldes, Sofia Cristina Martins (2022)
This study analyses the consideration of the principle of proportionality in the response of the European Union (EU) to online disinformation as a security threat. The use of disinformation in politics it is not new, but the current political, economic, social and mostly the technological landscape allows for disinformation to be created and spread more effectively. At the same time, democracies are particularly vulnerable to this threat, their openness enables an easier proliferation of disinformation, and their response is challenged by the need to safeguard the realisation of democratic principles and fundamental rights and freedoms. Consequently, democracies face the dilemma of effectively responding to disinformation, because of its impact in democratic life, without jeopardizing fundamental rights and freedoms that can potentially generate other insecurities. In this context, we use discourse analysis to analyse the security governance of online disinformation at EU level. The EU understands online disinformation as a complex and evolving threat to the survival of the European project at all levels, at the security, political, economic and social level. Furthermore, the EU recognises the dilemma of responding to disinformation, particularly because it may take multiple forms and thus demands a calibrated response. Therefore, the European Union responds to online disinformation through democratic deterrence, by measures of denial and punishment to prevent the success of interference and challenge the strategic calculus of the aggressor. We argue that the response of the European Union is mostly proportional, focused on protecting freedom of expression rather than prohibiting disinformation. Nevertheless, the limitations underlying the Code of Practice, the debunking strategy and the strategic communications, and the inconsistency associated with the recent suspension of Russian media have the potential to be exploited by adversaries, with implications for the effectiveness of the response. Therefore, although the European Union recognises the conundrum of responding effectively and proportionality to online disinformation, this balance remains at crossroads, with implications for the success of the response and the protection of fundamental rights and freedoms itself, which is the main objective in responding to online disinformation.